Behavioral Intention to Use Artificial Intelligence (AI) Among Accounting Students: Evaluating the Effect of Job Relevance - Krishnanraw, Jyashree; Kamisah, Ismail (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
This research meticulously evaluates the influence of job relevance on accounting undergraduates' behavioral intentions toward utilizing artificial intelligence (AI), scrutinizing the mediating role of perceived usefulness. Anchored in the extended technology acceptance model (TAM), this study employs a cross-sectional, survey-based methodology to gather data from 136 undergraduate students across various public and private Malaysian universities. The empirical evidence elucidates that job relevance positively influences the students’ behavioral intentions regarding AI integration. In tandem, perceived usefulness emerges as a significant mediator, revealing its critical role in this relationship, thus manifesting a partial mediation effect. The findings highlight the necessity of strategically reconfiguring accounting education curricula to incorporate pedagogical approaches aligned with the influential factors of job relevance and perceived usefulness, thereby intensifying students’ intentions to engage with AI in academic and professional settings. Such an educational evolution is paramount, equipping accounting students with the requisite competencies and insights to navigate the accounting profession’s rapidly transforming, technologically driven landscape.